Current applications of nanotechnology to develop plant growth inducer agents as an innovation strategy. (2nd January 2020) - Fincheira, Paola; Tortella, Gonzalo; Duran, Nelson; Seabra, Amedea B.; Rubilar, Olga
Abstract: Nanotechnology has been proposed as an important tool and strategy for applying new products in agriculture at the nanometer scale in order to improve the food crop at sustainability and productivity levels for contributing with the agriculture security. Nanoparticles (NPs) have been planted as an intelligent material with a large contact surface per unit mass respect to bulk-products, allowing its effect to be exerted with greater efficiency in a specific point on a plant target. Currently, NPs have been studied to be applied to various species of monocotyledonous and dicotyledonous plants. Some NPs properties such as concentration, shape, size, composition and surface functionality have the ability to regulate the NPs growth effects on the plant during germination and seedling stages under controlled and field conditions. Furthermore, several studies have tried to explain the mechanism of uptake, translocation and accumulation of NPs inside the plant at the organ and cell level, but further studies are needed to determine specific mechanisms and exact action. Nevertheless, evaluation of the toxicity effects of NPs on physiological indexes of the plant is needed to determine the effective dose without producing adverse effects on the plant and food chain. It is noteworthy that studies have indicated that nanoparticles, regardless of their nature, can be efficient inducers of plant growth. However, a series of laboratory tests are required to optimize their application conditions and their specific physiological impact on plants. In this review, we summarize the knowledge about NPs application to induce plant growth to direct future studies in order to propose NPs for technological innovation.